Low-tech, high impact: care for premature neonates in a district hospital in Burundi. A way forward to decrease neonatal mortality. (December 2016) - Ndelema, Brigitte; Bergh, Rafael; Manzi, Marcel; Boogaard, Wilma; Kosgei, Rose; Zuniga, Isabel; Juvenal, Manirampa; Reid, Anthony
Abstract Background Death among premature neonates contributes significantly to neonatal mortality which in turn represents approximately 40 % of paediatric mortality. Care for premature neonates is usually provided at the tertiary care level, and premature infants in rural areas often remain bereft of care. Here, we describe the characteristics and outcomes of premature neonates admitted to neonatal services in a district hospital in rural Burundi that also provided comprehensive emergency obstetric care. These services included a Neonatal Intensive Care Unit (NICU) and Kangaroo Mother Care (KMC) ward, and did not rely on high-tech interventions or specialist medical staff. Methods A retrospective descriptive study, using routine programme data of neonates (born at <32 weeks and 32–36 weeks of gestation), admitted to the NICU and/or KMC at Kabezi District Hospital. Results 437 premature babies were admitted to the neonatal services; of these, 134 (31 %) were born at <32 weeks, and 236 (54 %) at 32–36 weeks. There were 67 (15 %) with an unknown gestational age but with a clinical diagnosis of prematurity. Survival rates at hospital discharge were 62 % for the <32 weeks and 87 % for the 32–36 weeks groups; compared to respectively 30 and 50 % in the literature on neonates in low- and middle-income countries. Cause of death was categorised, non-specifically, as "Conditions associated with prematurity/low birth weight" for 90 % of the <32 weeks and 40 % of the 32–36 weeks of gestation groups. Conclusions Our study shows for the first time that providing neonatal care for premature babies is feasible at a district level in a resource-limited setting in Africa. High survival rates were observed, even in the absence of high-tech equipment or specialist neonatal physician staff. We suggest that these results were achieved through staff training, standardised protocols, simple but essential equipment, provision of complementary NICU and KMC units, and integration of the neonatal services with emergency obstetric care. This approach has the potential to considerably reduce overall neonatal mortality.